International Integration, Risk and the Welfare State - Torben M. Andersen (Institute for the Study of Labor (IZA), 2002)
How does international integration affect the welfare state? Does it call for a leaner or an expanded welfare state? International integration may affect the distortions caused by welfare state activities but also the risks motivating social insurance mechanisms. This paper addresses these potentially counteracting effects in a fully specified intertemporal twocountry stochastic endowment model focusing on the implications of product market integration reducing trade frictions across national product markets. It is shown that lower trade frictions may increase the marginal costs of public funds, which gives an argument for reducing (steady-state) public consumption. However, tighter integration of product markets unambiguously leads to more variability in private consumption, and this gives a case for expanding the social insurance provided via state-contingent public sector activities (automatic stabilizers).
Keywords: H11; F10; E30; 330; Trade frictions; risk-sharing; optimal public consumption; social insurance; Globalisierung; Außenhandelsliberalisierung; Sozialstaat; Schock; Risiko; Theorie